The Neuroprotective Role of MiR‐124‐3p in a 6‐Hydroxydopamine‐Induced Cell Model of Parkinson's Disease via the Regulation of ANAX5 - Dong, Rui‐Fang; Zhang, Bing; Tai, Li‐Wen; Liu, Hong‐Mei; Shi, Fang‐Kun; Liu, Ning‐Ning (Journal of cellular biochemistry, 2018)
ABSTRACT Parkinson's disease (PD), the second most common neurodegenerative disorder, is characterized by a progressive loss of dopaminergic neurons in the midbrain. Several pathogenetic factors have been involved in the onset and progression of PD, including inflammation, oxidative stress, unfolded protein accumulation, and apoptosis. Ample evidence indicates that miRNAs could regulate post‐transcriptional gene expression and neuronal disease. In this study, we evaluated the effects and mechanism of miR‐124‐3p on 6‐hydroxydopamine (6‐OHDA)‐induced neurotoxicity in PC12 cells and SH‐SY5Y cells. qRT‐PCR results showed that the level of miR‐124‐3p was downregulated in 6‐OHDA‐treated PC12 and SH‐SY5Y cells, and overexpression of miR‐124‐3p significantly promoted the cell viability of 6‐OHDA‐treated PC12 and SH‐SY5Y cells, whereas miR‐124‐3p inhibitor reversed these effects. In addition, PC12 or SH‐SY5Y cells were treated with miR‐124‐3p mimics or inhibitors following 6‐OHDA administration, which mediated cell apoptosis and downregulation or upregulation of Caspase‐3 activity, respectively. A luciferase reporter assay revealed that annexinA5 (ANXA5) is a direct target gene of miR‐124‐3p, and miR‐124‐3p overexpression markedly downregulated the level of ANXA5. Strikingly, further analysis showed that miR‐124‐3p enhanced the viability of 6‐OHDA‐treated PC12 or SH‐SY5Y cells by targeting ANXA5, which was associated with the stimulation of the ERK pathway. This study revealed that miR‐124‐3p may play a neuroprotective role in PD; this observation may provide new ideas and therapeutic targets for PD. J. Cell. Biochem. 119: 269–277, 2018. © 2017 Wiley Periodicals, Inc. This study revealed that miR‐124‐3p may play a neuroprotective role in PD; this observation may provide new ideas and therapeutic targets for PD.